Prevention of football injuries - Kirkendall, D. T.; Junge, A.; Dvorak, J. (Asian Journal of Sports Medicine, 2010)
Every sport has a unique profile of injury and risk of injury. In recent years, there have been numerous attempts at conducting injury prevention trials for specific injuries or for injuries within specific sports to provide evidence useful to the sports medicine and sport community. Football has been a focus of a number of randomized injury prevention trials.